Ledstillingsvariation i amerikadanske hovedsætninger med topikalisering - Kühl, Karoline; Heegård, Jan (Ny forskning i grammatik, 2016)
Danish qualifies as a V2-language. Inversion of subject and finite verb is mandatory in topicalized declarative main clauses (topic-V-S). In American Danish, however, topicalized declaratives show standardlike word order to a large extent, but also considerable non-inversion (topic-S-V). This word order variation mirrors the syntactical patterns of Danish and American English. Based on an American Danish corpus of 103.000 words, we pinpoint the syntactical contexts that are affected by variation, those resistant to change and influential factors. Sentence-initial adverbial connectors and topicalized English elements favour English word order, while left dislocation constructions with an anaphoric particle are very resistant to change and there is a (weak) correlation between longer topics and Standard Danish word order. Sociolinguistics variables do not show any effect at all.